A subset of CD1c+ dendritic cells is increased in patients with tuberculosis and promotes Th17 cell polarization. (December 2018) - Liu, Yanhua; Wang, Ruo; Jiang, Jing; Cao, Zhihong; Zhai, Fei; Sun, Weiguo; Cheng, Xiaoxing
Abstract: The role of primary subsets of DCs in Mycobacterium tuberculosis infection in humans is incompletely understood. In this study, we identified a CD1c DC subset with phenotype of CD1c + CD11c + CD19 − CD11b + that was significantly increased in tuberculous pleural effusions and in peripheral blood from patients with TB compared with that from healthy controls (p < 0.0001). Sputum smear/culture-positive patients with tuberculosis had significantly higher frequency of CD1c + CD11b + DC subset than sputum smear/culture-negative patients (p < 0.0001). After effective anti-TB chemotherapy, the frequency of CD1c + CD11b + DC subset in peripheral blood and tuberculous pleural effusions was decreased. CD1c + CD11b + DC subset from tuberculous pleural effusions expressed higher levels of TLR2, TLR4, CD172a, CD206 and FcεRⅠ, but lower levels of CD80, CD83 and CD86 compared with CD1c + CD11b − DC subset. Expression of IL-1β, IL-6, IL-8, IL-23, TNF-α, IFN-γ and TGF-β mRNA in CD1c + CD11b + DCs was higher than in CD1c + CD11b − DC subset. Co-culture of autologous naive CD4 + T cells with sorted CD1c + CD11b + DCs expressed significantly increased levels of IL-17A and RORγt transcripts as compared with those co-cultured with CD11b − subset. In conclusion, a CD1c + CD11b + DC subset with elevated frequency in patients with tuberculosis was identified and it promoted Th17 cell differentiation.